IMPROVING STUDENTS’ SPEAKING PARTICIPATION IN ASKING QUESTION BY USING PLANTED QUESTION TECHNIQUE - Ramadhan, Ari; Apriliaswati, Rahayu; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research discussed the use of planted question technique to improve students’ speaking participation in asking question. This research was conducted to the eighth grade B students of MTs Negeri 1 MempawahHilir. There were thirty six students.The method used was the classroom action research. The findings showed that the percentage of students’ speaking participation in asking question in the first cycle was 16.6% (poor). It kept going up to the level of 38.8% (poor) in the second cycle, and in the third cycle, the students’ percentage of students’ speaking participation in asking question was improving to the level of 63.8% (average to good). The field note that was fulfilled by the collaborator also showed the same result. The students’ participation showed the improvement from cycle to cycle. They were able to erase their shyness and asked question by using English. All of the goals in teaching and learning process have been fulfilled in the third cycle. Through this research, the students’ speaking participation in asking question was improved in the number of students who was participating in asking question. Keywords : Participation, Asking, Planted Question Technique Abstrak: Penelitian ini menjelaskan penggunaan tehnik pertanyaan yang ditanamkan untuk meningkatkan partisipasi bertanya siswa dalam mengajukan pertanyaan. Penelitian ini dilakukan kepada siswa kelas 8B MTs Negeri 1 Mempawah Hilir yang berjumalah 36 siswa. Metode yang digunakan adalah penelitian tindakan kelas. Hasil penelitian menunjukkan bahwa persentase partisipasi bertanya siswa dalam mengajukan pertanyaan pada sikluspertamaadalah 16.6% (rendah).Kemudian persentase tersebut naik ke angka 38.8% (rendah) pada siklu skedua. Dan pada siklus ketiga, persentase partisipasi bertanya siswa dalam mengajukan pertanyaan meningkat ke angka 63.8% (rata-rata menuju baik). Catatan lapangan yang ditulis oleh kolaborator juga menunjukkan hasil yang sama. Partisipasi  siswa menunjukkan peningkatan pada setiap siklus, sehingga mereka bias menghilangkan rasa malu mereka untuk bertanya menggunakan Bahasa Inggris. Seluruh target dalam proses belajar mengajar sudah terpenuhi pada siklus ketiga. Melalui penelitian ini, partisipasi bertanya siswa dalam mengajukan pertanyaan meningkat dalam hal jumlah siswa yang berpartisipasimengajukanpertanyaan. Kata Kunci :Partisipasi, Bertanya, Tehnik Pertanyaan Ditanamkan